Anonymous

# Need help in calculus reviewer?

Let f (x,y,z) = zxy + 2x. Use this definition of f to find the given functions.

Enter the fully simplified answer.

(a)

f(x+3y , x-3y , 2x^2)

= ???

(b)

f(4xy, 7y/x, 3xz)

= ???

TYIA ^^

### 1 Answer

Relevance

- llafferLv 71 month ago
f(x, y, z) = zxy + 2x

Just substitute and simplify:

f(x + 3y, x - 3y, 2x²)

Substitute the first into "x", second into "y", etc.:

f(x, y, z) = zxy + 2x

f(x + 3y, x - 3y, 2x²) = 2x²(x + 3y)(x - 3y) + 2(x + 3y)

f(x + 3y, x - 3y, 2x²) = 2x²(x² - 3xy + 3xy - 9y²) + 2(x + 3y)

f(x + 3y, x - 3y, 2x²) = 2x²(x² - 9y²) + 2(x + 3y)

f(x + 3y, x - 3y, 2x²) = 2x⁴ - 18x²y² + 2x + 6y

I'll leave the other one for you to work.

Still have questions? Get answers by asking now.